On-location recording techniques - Bartlett, Bruce (Focal Press, 1999)
Dividing classical and popular music recording into two distinct sections, this book focuses on the special techniques used for recording outside the confines of the studio and shows readers how to interface with sound reinforcement equipment in the hall or club. Recent developments in portable digital multitrack recorders and high-quality mixers have made on-location recording feasible for all recording engineers. Many bands want to be recorded in concert because they feel that is when they play their best music. The engineer's job is to capture that performance on tape and bring it back live.